Analysis of the inelastic lateral - torsional buckling resistances of steel truss members with global and local imperfections - Nguyen Duc BINH; Bui Tien THANH; Pham Van PHE; Isabel B VALENTE; José C MATOS (Journal of Materials and Engineering Structures)
The local and global imperfections of I-shaped steel beams are known to significantly impact the load-carrying capacity of the structure. This is particularly critical for structures subjected to heavy loads, where these factors must be meticulously controlled to prevent potential failures. Therefore, the objective of this project is to describe a numerical analysis that was conducted to evaluate the influence that initial global and local flaws have on the inelastic buckling resistances of steel truss members that are used in steel bridges. These numerical studies are based on Abaqus, and they have been validated quite well against the data that are now available. After that, the numerical models are utilized in order to assess the inelastic buckling resistances of the system, taking into consideration four distinct sorts of initial global and local imperfections which are feasible. The numerical results are compared to the standard evaluations, which are also examined and evaluated. In addition, parametric investigations of the impact of the thicknesses of the web and flange on the inelastic buckling resistances are carried out as part of the current research. The strengthening techniques assessed in this research can serve as a foundation for engineers to implement in actual steel beam structures.